Development and validation of a liquid chromatography‐tandem mass spectrometry method for simultaneous detection of 10 illicit drugs in oral fluid collected with FLOQSwabs™ and application to real samples. Issue 6 (17th January 2019) - Fabresse, Nicolas; Aouad, Hassan; Knapp, Adeline; Mayer, Charlotte; Etting, Isabelle; Larabi, Islam Amine; Alvarez, Jean‐Claude
Abstract: According to French law, the roadside testing for drugs of abuse (DOA) should be performed in oral fluid (OF) using an immunological screening kit. If the screening is positive, confirmation has to be done in OF collected by a special swab, called the FLOQSwab™ (FS). Unlike other sampling kits, this device was not designed to collect OF since it does not contain an elution buffer. An analytical method was developed for the simultaneous detection of 10 DOA under control in France: tetrahydrocannabinol (THC) at 1 ng/mL, and cocaine, benzoylecgonine (BZE), morphine, 6‐monoacetylmorphine (6‐MAM), amphetamine, methamphetamine, 3, 4‐methylenedioxy‐ N ‐ethylamphetamine (MDEA), 3, 4‐methylenedioxyamphetamine (MDA), and 3, 4‐methylenedioxy‐ N ‐methylamphetamine (MDMA) at 10 ng/mL. Samples were eluted using the Quantisal ® buffer and extracted by liquid–liquid extraction for THC and by solid‐phase extraction for the remaining analytes. Analyses were performed by ultra‐high performance liquid chromatography coupled with tandem mass spectrometry (UHPLC–MS/MS). The validated method made it possible to detect the concentrations required by law and was successfully applied to samples from drivers who screened positive. The main limitations of this kit are the large variability of the collected OF volume and the poor stability of DOA in OF, requiring the use of a conservation buffer. Abstract : The roadside testing for drugs of abuse (DOA) in France should be performed in oral fluid (OF) using an immunological screening kit and confirmation has to be done in OF collected by a special swab, called the FLOQSwab™. Unlike other sampling kits, this device was not designed to collect OF. An LC–MS/MS method was developed for the simultaneous detection of 10 DOA. The method was validated and successfully applied to samples from drivers.